Ungkap Potensi Kawasan Ekonomi Khusus dalam Mewujudkan Ekonomi Inklusif - Chrisna Satya Wardhana (Syntax Corporation Indonesia, 2024)
This research examines the potential of Special Economic Zones (KEK) in realizing an inclusive economy in Indonesia through literature observations. The main findings show that SEZs act as a catalyst for economic growth by attracting investment and creating a multiplier effect for the local economy. To realize an inclusive economy, SEZs need to integrate region-based development, implement a sustainable economy, and strengthen the principle of linkages with local economic sectors. However, there are challenges such as concentration of benefits in large companies, exploitation of resources, and weakening integration with local economies. The proposed solutions include implementing a circular economy, supporting local entrepreneurship, and increasing community access to financing, training and business networks. Comprehensive efforts are needed to maximize the potential of SEZs in achieving a sustainable, inclusive economy.